The Jihad against Oligarchy: Developing an Inclusive Democracy Based on Islamic Social Justice Values in Indonesia - Novitasari, Uffi (Journal of Transcendental Law, 2025)
This research aims to analyze the influence of oligarchy on democracy and social justice in Indonesia from Islamic perspective. This research employed the descriptive-qualitative approach using literary and case study methods. The data were obtained from various academic literary materials, journal articles, as well as analyses of concrete cases, such as oligarchic practices in the political, economic, and religious sectors. Research findings showed that oligarchy fundamentally violates the Islamic principles of justice, equality, deliberation (syura), and responsibility. Oligarchy has manipulated the political-economic system through the practice of expensive political financing, the use of the state’s resources, the use of descendants of the kiai’s lineage (Islamic religious figures) in political elections, the weakening of anti-corruption institutions (such as the Corruption Eradication Commission), as well as their domination in public positions. Cases such as the election of village heads and regents who are descendants of the kiai lineage, colored with the practice of power dynasty and natural resource exploitation by political elites, reflect the negative impacts of oligarchy’s dominance. To overcome this problem, there is a need for an integration of Islamic values into the democratic practices dominated by oligarchic groups, as well as an institutional reformation to achieve transparency and accountability. Even so, the success of reformation highly depends on the courage of political actors to free themselves from oligarchic pressures while prioritizing the people’s interests. Apart from that, the difficulty to integrate Islamic values happens due to public officials’ lack of Islamic political ethics. Therefore, building a democratic political and economic system based on the value of Islamic social justice becomes the absolute requirement for carrying out jihad against the oligarchic group.